The Effect of Negative User-Generated Content Reviews in the Form of Testimonials on Interest in Visiting Borobudur Temple, Prambanan, and Ratu Boko Palace - Wingkie Nusanti (Publikasi Indonesia, 2024)
Historical tourism in Indonesia, especially destinations such as Borobudur Temple, Prambanan, and Ratu Boko Palace, has great potential to attract both domestic and international tourists. However, negative reviews that come from user-generated content in the form of testimonials are often a factor that can affect the interest of tourist visits. This study aims to analyze the impact of negative reviews on interest in tourist visits to these historical destinations. This study aims to eval_uate the extent to which negative reviews affect interest in tourist visits to three main cultural destinations in Indonesia: Borobudur Temple, Prambanan Temple, and Ratu Boko Palace. This study uses a descriptive quantitative method by collecting data through a survey of 58 respondents who have visited the three destinations. The data was processed using SPSS software to test the validity, reliability, and influence of negative reviews on the interest of tourist visits. The results of the analysis showed that negative reviews did not significantly affect the interest of tourists visiting Borobudur Temple, Prambanan, and Ratu Boko Palace. All three destinations remain the top choice for tourists, despite the negative reviews, mainly due to their strong historical reputation and visual appeal. This study concludes that negative reviews do not have a significant influence on the interest in tourist visits to the historical destinations of Borobudur, Prambanan, and Ratu Boko Palace. Therefore, destination managers are advised to continue to pay attention to negative reviews as eval_uation material but do not need to worry too much about the impact on tourist visits.